FENOMENA PENIMBUNAN BBM BERSUBSIDI DI KOTA PEKANBARU - Sobri S.IP.,MA; Fauzan Nur (SISI LAIN REALITA, 2016)
In the years 2013 to 20014, revealed there were 72 cases of hoarding subsidized fuel in Pekanbaru. In a number of very pantastis to measure the extent of the area of Pekanbaru. At least there are several indications supporting the presence of the phenomenon of hoarding subsidized fuel in Pekanbaru include: factors opportunities, linking between the demand by business operators on the one hand, easy to obtain fuel at the pump through unscrupulous employees with mode-specific mode on the other hand, as well as the role of local police officers as security at a time furnisher. The next factor is the lack of oversight by the government and authorities in the field and lack of legal sanctions in providing a deterrent effect for offenders caught.